Environmental Tax Morale, Governance Signals, and Corporate Tax Aggressiveness - Amri Amrulloh; Yopie Diondy Kurniawan (Inovasi Analisis Data, 2025)
Purpose – This paper explores the role of civic environmental tax morale and governance signals in explaining corporate tax avoidance via managerial and organizational moral processes. Design/methodology/approach – The work tests for direct, mediating and moderating relations within a behavioral governance model by means of structural equation modeling. Findings – Results suggest that the strength of environmental tax morale materially declines corporate tax avoidance, mostly by the indirect methods instead of direct managerial decision. Empirical results reflect managerial tax morale, ethical tax culture and reputational risk sensitivity as core mechanisms that transform normative influence into conforming tax behavior. Governance signals tax enforcement salience, governance transparency and regulatory clarity – reinforce these moral mechanisms but their direct paths to tax avoidance are mixed. The findings also indicate that the income-shifting opportunity attenuates moral constraints by allowing firms to decouple moral intent from actual tax behavior, especially when structural flexibility is high. Taken together, the findings provide support for a multilayered governance process in which social norms and institutional signals simultaneously influence tax decisions via internalized managerial and cultural processes. Originality/value – This contribution to tax governance literature consolidates environmental tax morale in a joint model with governance signaling and moral internalization mechanisms, thus moving beyond conventional deterrence-based accounts. Research Implications – The findings reinforce the necessity to consider normative and behavioural elements in corporate tax research, and suggest a call for governance mechanisms that support ethical decision making beyond (reported) enforcement intensity.